ANALISA KEBUTUHAN RUANG PARKIR FAKULTAS TEKNIK UNIVERSITAS PATTIMURA - Buyang, Julius; Buyang, Christy Gerry (Journal Agregate, 2023)
The growth of campus population made an imbalance between the number of vehicles and the availability of parking spaces. This study aims to analyze the need for parking space for the next 5 years and examine the existing number of parking lots at the Faculty of Engineering, Universitas Pattimura Ambon. The problem of the need for parking space is important because the growth of students and employees in the Faculty of Engineering greatly influences motorized vehicles and cars, but the increase in vehicle users is not matched by efficient parking lots/facilities. Therefore it is necessary to research the problem by using an analysis of parking space requirements and parking space unit. The research method used is field surveys, interviews, and academic data to collect data on the growth in the number of students, lecturers, and staff. The results of the study show that in the next 5 years, there is a projected significant increase in the number of vehicles in the Faculty of Engineering. The estimated growth in these vehicles will lead to an increase in the need for parking spaces in 2028 of 220 for motorcycles and 23 for cars, from the current number of existing parking lots. Based on the results of the analysis, it is suggested that the Faculty of Engineering, Universitas Pattimura Ambon take appropriate planning and policy development actions to deal with the problem of parking space requirements in the future.